STUDENT EFFECTIVE COMMUNICATION - Wida Wulandari (Jurnal Pendidikan Ilmu Sosial, 2023)
Knowing the link and strength of elements that influence good communication is a criterion in the research. The approach employed is an explanatory survey method using data gathering techniques based on a Likert scale via questionnaires from The Ombuds Office of the University of Louisville. The obtained data is processed using SPSS 23 data testing software and analyzed with the SEM multiple regression techniques for CFA factor analysis. Data analysis reveals that 65% and 78.1% of the understanding and expression elements have a very substantial influence on middle school students' successful communication abilities.